Anais Do 10. Congresso Brasileiro De Inteligência Computacional 2016
DOI: 10.21528/cbic2011-27.1
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Forecast Using Data Mining Techniques On Hourly Evolution Of The Convective Available Potential Energy

Abstract: This study presents a method developed for lightning forecasting in eastern Amazonia, based on the estimates of the hourly evolution of the convective available potential energy (CAPE). The CAPE is a computed index of the air stability situation over a given area of the Earth. This parameter is determined from vertical profiles of temperature and humidity of the atmosphere, obtained through radiosondes. The CAPE values may also be estimated during the period between soundings, by using the meteorological varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…8. DT general structure [34] In DT, the root node represents the attribute. The inner node indicates the test or evaluation of a property.…”
Section: Decision Tree (Dt)mentioning
confidence: 99%
“…8. DT general structure [34] In DT, the root node represents the attribute. The inner node indicates the test or evaluation of a property.…”
Section: Decision Tree (Dt)mentioning
confidence: 99%
“…Besides their limitations, DTs are able to solve a wide array of classification problems. For instance, among their applications can be cited citation networks [16], pharmaceutical manufacturing process [17], modelling building energy demand [18], weather forecast [19], diagnosis of diseases [8], [9], detection of forest fires [20], agriculture [21], finance [22], computer vision and many more [23].…”
Section: Decision Treesmentioning
confidence: 99%
“…with LFC the Level of Free Convection, EL the Equilibrium Level, θe the equivalent potential temperature of the air parcel and θes the saturated equivalent potential temperature of the atmospheric environment. CAPE stands for positive differences between θe and θes meaning that the pseudo-adiabatic of the displaced air parcel is warmer than the environment resulting to instability situations (Sá et al 2011;Das 2017). In other words, it is the amount of energy an airparcel would have in case it were vertically lifted to a certain height in the atmosphere.…”
Section: Convective Potential Available Energymentioning
confidence: 99%
“…In the literature there is a great number of works based on the artificial intelligence and data mining techniques (e.g. Sá et al 2011;Bates et al 2018;Schön et al 2019;Mostajabi et al 2019;Shrestha et al 2019). An extensive survey of several research papers can be found in Bala et al 2017. In this work we examine the occurrence of extreme wind gusts around a wind power plant, located in a hilly region of Western Greece, based on the presence of cumulonimbus clouds and lightning activity.…”
Section: Introductionmentioning
confidence: 99%